2010
DOI: 10.1007/s11240-010-9696-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of cytokinins in shoot organogenesis in apple

Abstract: Effective regeneration in vitro is a necessary precondition for the implementation of different biotechnological approaches in plant breeding. Numerous studies have reported on regeneration from apple somatic tissues, and organogenesis has been proved to be influenced by several factors including mother shoots (genotype, size, type, and age of explant), in vitro conditions (dark period, light intensity, and quality), and others (wounding, orientation of leaf explants). However, one of the most important factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
1
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(82 citation statements)
references
References 74 publications
7
68
1
6
Order By: Relevance
“…This result was corroborated by Žiauka and Kuusienė (2010), who observed complete inhibition in root formation when Populus tremula L. nodal segments were treated with high doses of paclobutrazol, an antagonist molecule of gibberellin synthesis, indicating that GAs, in low concentrations, may become beneficial to root development. Apparently, reduced doses of GA 3 , when associated with BAP, increase the effectiveness of in vitro propagation processes, particularly in explants elongation and root formation phases (Pati et al, 2006;Magyar-Tábori et al, 2010). However, in this study, the beneficial effects of gibberellins were not observed for M. pudica.…”
Section: Cultured In Vitrocontrasting
confidence: 72%
“…This result was corroborated by Žiauka and Kuusienė (2010), who observed complete inhibition in root formation when Populus tremula L. nodal segments were treated with high doses of paclobutrazol, an antagonist molecule of gibberellin synthesis, indicating that GAs, in low concentrations, may become beneficial to root development. Apparently, reduced doses of GA 3 , when associated with BAP, increase the effectiveness of in vitro propagation processes, particularly in explants elongation and root formation phases (Pati et al, 2006;Magyar-Tábori et al, 2010). However, in this study, the beneficial effects of gibberellins were not observed for M. pudica.…”
Section: Cultured In Vitrocontrasting
confidence: 72%
“…Other cytokinins such as Zea, 2iP and kinetin [37] are less commonly used, and the use of phenylurea derivatives such as thidiazuron and N-2-chloro-4-pyridyl)-N-phenylurea (CPPU) is sometimes described on shoot proliferation in pear cultures [38]. However, theeffectiveness of any of these cytokinins in the multiplication medium will depend primarily on the genotype of the cultivar [28].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the risk of mutation in clones derived from axillary buds is much lower than the risk of mutation during organogenesis from callus. Both BA and TDZ are the most frequently used cytokinins in apple regeneration and they have been compared in several studies [28]. TDZ has been found to be more effective than BA for shoot regeneration in numerous trials [25] [41] [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the relationship between the applied plant growth regulators and the explant's ability to respond to the stimuli provided by the plant growth regulators determines organogenesis (Find et al 2014). Therefore, successful plant regeneration in tissue culture involves multiple processes, including signal transduction and perception of stimuli from plant growth regulators, redifferentiation of the dedifferentiated tissues, subsequent cell division, and organization to form organs (i.e., root, shoot) (Magyar-Tábori et al 2010, Almeida et al 2015. Cytokinins added to the regeneration medium can enhance cell competence for the development of new shoots and therefore increase the number and frequency of regenerating shoots and their subsequent growth rate (Hartmann et al 2011).…”
Section: Introductionmentioning
confidence: 99%